2014
DOI: 10.1016/j.dam.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

The packing coloring of distance graphs D(k,t)

Abstract: The packing chromatic number χ ρ (G) of a graph G is the smallest integer p such that vertices of G can be partitioned into disjoint classes X 1 , ..., X p where vertices in X i have pairwise distance greater than i. For k < t we study the packing chromatic number of infinite distance graphs D(k, t), i.e. graphs with the set Z of integers as vertex set and in which two distinct vertices i, j ∈ Z are adjacent if and only if |i − j| ∈ {k, t}.We generalize results by Ekstein et al. for graphs D(1, t). For suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The study of a packing coloring of distance graphs Dðk; tÞ was initiated by Togni [13] who determined the packing chromatic number of Dð1; tÞ for small values of t. Distance graphs were further investigated by Ekstein et al in [14,15], where some more results on the packing chromatic number of Dð1; tÞ and Dðk; tÞ are given.…”
Section: Introductionmentioning
confidence: 99%
“…The study of a packing coloring of distance graphs Dðk; tÞ was initiated by Togni [13] who determined the packing chromatic number of Dð1; tÞ for small values of t. Distance graphs were further investigated by Ekstein et al in [14,15], where some more results on the packing chromatic number of Dð1; tÞ and Dðk; tÞ are given.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these bounds were improved by Ekstein, Holub, and Lidický [22]; the improved bounds are presented in the same table in bold font. Next, Ekstein, Holub, and Togni [23] further improved two values; these are the underlined items in the table. Finally, Shao and Vesel [60] improved three of the upper bounds; these improvements are marked with stars in the table.…”
Section: Distance Graphsmentioning
confidence: 99%
“…This was the key observation in proving the next result. Ekstein et al [23] further improved the bounds on the packing chromatic number of some specific distance graphs as follows. The particular case when k = 1 of Theorem 6.10 was earlier deduced in [22,Corollary 4].…”
Section: Distance Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiala and Golovach have shown that the decision version of the packing chromatic number is NP-complete even in the class of trees [12]. Packing coloring of some other classes of graphs, such as the distance graphs [11,22,25], hypercubes [26], subdivision graphs of subcubic graphs [4,10,15], and still other classes of graphs [2,18,20] was also studied.…”
Section: Introductionmentioning
confidence: 99%